MICRO TEXTUAL ANALYSIS ON FIRST PRESIDENTIAL SPEECHES IN U.S. PRESIDENT’S INAUGURAL ADDRESS - M Nizar Zulhamsyah; Agwin Degaf (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
In an inauguration day, a president should deliver his first speech which often consists of essential matters for him to convey his vision, mission and strategies in leading the nation which are significant, vital and sometimes different from one president to others. In this paper, first presidential speeches performed by Barack Obama and Donald Trump in the U.S. President’s inaugural address are studied through micro textual analysis. This study results the difference and diverse characteristics found from analysing micro textual element, comprising stylistic, syntactic and semantic element employed by both presidents. It is expected that the study contributes theoretically to develop the use of micro textual structure on disclosing one’s ideology and practically improve the way people perceive one’s speech because it always has an idea which is rather delicate to understand.